2014
DOI: 10.1111/1475-6773.12258
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Intensive Care Management for Disabled Medicaid Beneficiaries with High Health Care Costs

Abstract: Objective. To evaluate outcomes of a registered nurse-led care management intervention for disabled Medicaid beneficiaries with high health care costs. Data Sources/Study Setting. Washington State Department of Social and Health Services Client Outcomes Database, 2008Database, -2011 Study Design. In a randomized controlled trial with intent-to-treat analysis, outcomes were compared for the intervention (n = 557) and control groups (n = 563). A quasiexperimental subanalysis compared outcomes for program partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…In one study (44), high intensity case management seemed to lead to fewer months homeless (mean number of months per 100 months homeless). However, the 95% confidence interval indicates that high intensity case management might make little or no difference the amount of time spent homeless (results as reported in original publication: n=-1.5 [95% CI -4.3 to 1.3], p=0.29).…”
Section: Figure 4: Number Of Days Homeless 12-24 Months High Intensmentioning
confidence: 98%
See 3 more Smart Citations
“…In one study (44), high intensity case management seemed to lead to fewer months homeless (mean number of months per 100 months homeless). However, the 95% confidence interval indicates that high intensity case management might make little or no difference the amount of time spent homeless (results as reported in original publication: n=-1.5 [95% CI -4.3 to 1.3], p=0.29).…”
Section: Figure 4: Number Of Days Homeless 12-24 Months High Intensmentioning
confidence: 98%
“…Thirteen of the included studies examined homelessness (39, 44-46, 48, 50, 54, 59, 60, 70, 71, 80, 83). Seven studies reported outcomes related to length of time homeless, either in terms of number of months (44) or number of days (39,46,50,60,71,80).…”
Section: Primary Outcome: Homelessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies of intensive care management of socially and medically high‐risk patients have shown a lack of cost savings with improved access and increased utilization in the short term (Bell et al. ). However, over several years, there may be a cost savings from care management programs for patients with behavioral health issues (Unutzer et al.…”
Section: Discussionmentioning
confidence: 99%